2018
DOI: 10.1521/pedi.2018.32.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Competing Theories of Borderline Personality Disorder

Abstract: The authors review four theories that propose different conceptualizations of borderline personality disorder's (BPD) core psychopathology: excess aggression, emotional dysregulation, failed mentalization, and interpersonal hypersensitivity. The theories are compared in their ability to explain BPD's coaggregation of four usually distinct sectors of psychopathology, their high overlap with other disorders, their ability to distinguish BPD from other disorders, their integration of heritability, and their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
1
40
0
7
Order By: Relevance
“…A large body of research has shown that borderline personality is strongly related to neuroticism and/or a general factor of maladaptive personality (Samuel & Widiger, ; Sharp et al, ; Trull, Widiger, Lynam, & Costa, ; Wright, Hopwood, et al, ). Yet, there is also a strong feeling in clinical circles that borderline PD should be retained in the lexicon (Gunderson, Fruzetti, Unruh, & Choi‐Kahn, in press; Lieb, Zanarini, Schmahl, Linehan, & Bohus, ; Zimmerman, )—there are treatments, clinics, advocacy groups, third‐party reimbursement schedules, scientific societies, and journals organized around the concept. Researchers and clinicians invested in borderline PD are loathe to let it go despite convincing evidence that it can be more effectively captured by trait concepts, at least when it is conceptualized as a stable disposition.…”
Section: Personality Disorders As Traitsmentioning
confidence: 99%
“…A large body of research has shown that borderline personality is strongly related to neuroticism and/or a general factor of maladaptive personality (Samuel & Widiger, ; Sharp et al, ; Trull, Widiger, Lynam, & Costa, ; Wright, Hopwood, et al, ). Yet, there is also a strong feeling in clinical circles that borderline PD should be retained in the lexicon (Gunderson, Fruzetti, Unruh, & Choi‐Kahn, in press; Lieb, Zanarini, Schmahl, Linehan, & Bohus, ; Zimmerman, )—there are treatments, clinics, advocacy groups, third‐party reimbursement schedules, scientific societies, and journals organized around the concept. Researchers and clinicians invested in borderline PD are loathe to let it go despite convincing evidence that it can be more effectively captured by trait concepts, at least when it is conceptualized as a stable disposition.…”
Section: Personality Disorders As Traitsmentioning
confidence: 99%
“…¿Cómo se implementa el trabajo en psicodrama bipersonal con personas diagnosticadas como T.L.P.? Antes de dar una respuesta, y aunque no profundicemos en las características del TLP (véase Bateman y Fonagy, 2016;Fonagy, Luyten y Allison, 2015;Gunderson, Fruzzetti, Brandon, y Choi-Kain, 2018;Kernberg, 1967;Linehan, 1993).…”
Section: Psicodrama Bipersonal En La Atención a Trastorno Límite De Punclassified
“…La última de las teorías más relevantes sobre TLP, es la de Gunderson et al (2018). El autor nos dice que el elemento esencial explicativo del TLP, se ubica en la Hipersensibilidad Interpersonal.…”
Section: Psicodrama Bipersonal En La Atención a Trastorno Límite De Punclassified
“…Far fewer studies evaluated psychic health in offspring of patients suffering from a borderline personality disorder (BPD). BPD is a complex disorder whose etiology is believed to be the result of gene-environment interactions, with early-life adversities playing a major role (Gunderson, Fruzzetti, Unruh, & Choi-Kain, 2018). Weiss et al (1996) reported ADHD as being the most frequent disorder among a cohort of 21 offspring of mothers with BPD (in 43% of the BPD offspring sample).…”
Section: Introductionmentioning
confidence: 99%